Pengaruh Variasi Temperatur Austenit Pengujian Jominy Test Pada Sifat Hardenability Baja ST 90 - Azmal Azmal; Dwi Handoko; Masril Masril; Eligius Ilhamdi (Politeknik Negeri Pontianak, 2021)
The purpose of this research is to obtain information about the hardness value (hardening) and changes in microstructure as well as changes in the properties of the material at a temperature variation of 600℃ to 900℃. The method used in this study is an experimental method, where the material used is ST.90 steel, and Jominy testing. 5 samples were made at each temperature 22℃, 600℃, 700℃, 800℃, and 900℃ with the type of heat treatment in the hardening process. The test results for Vickers hardness decreased by an average of 33.99 HV or 31% and the carbon content decreased by an average of 0.19. or 48% of the normalizing process is not done. Based on the data above, it shows that the results of the Vickers hardness test and chemical composition with the hardening process of ST.90 steel, which are heated at 600℃, 700℃, 800℃, and 900℃ respectively, each temperature is reached and stopped with 60 minutes. In order for phase transformation to occur in all parts of the material, then the cooling process is carried out using the Jominy test, showing the mechanical strength, namely the Vickers hardness test decreases by 23% and the carbon content decreases at 37%.